Kemampuan Koneksi Matematis dan Peta Konsep Siswa SMP melaluiModel Pembelajaran Advance Organizer - Samsul Bahri; Rahmah Johar; M. Duskri (Universitas Syiah Kuala, 2014)
Mathematics is structured that any material science related. To understand the interrelated mathematical material this needs the capability mathematics. Connection ability mathematical connection is very important and is one of the capabilities that must be owned by a person and the unavoidable presence when someone studying mathematics. This study aims to determine: Is the increase in mathematical connection ability of students who obtain advance learning through learning model organizer better than students who received conventional learning, interaction learning model initial advance organizer with the ability of students to increase the ability of students' mathematical connections, and describes the ability to make map concept of junior high school students who acquire learning through advanced learning model organizer. This research uses an experimental quantitative methods approach. The population in this study were all seventh grade students of SMP Negeri 5 Lhokseumawe consisting of ten classes. As a sample of randomly selected classes will be the subject of study chosen as an experimental class VII1 class and class VII5 control. Instrumen elected as class research in this study is testing the ability to connect mathematical description shaped totaled about 5 grains soal. Koefisien the reliability test of 0.672 koefisien reliabilitas tests showed high levels. The results showed that: (1) Increased ability of students being taught mathematical connection with the advance organizer learning model is better than the students who obtain conventional overall learning and based on the level of the student. (2) There is no interaction learning model initial advance organizer with the ability of students to increase the ability of students' mathematical connections. (3) The ability of the students create concept maps in learning mathematics through advanced learning model organizer adalah well. Keywords: Learning Model Advance Organizer, Ability Mathematical Connections, and Concept Map